Adolescent stress experiences over time study (ASETS) protocol: design and methods of a prospective longitudinal study of sexual minority adolescents in the USA. Issue 3 (9th March 2022) - Schrager, Sheree M; Mamey, Mary Rose; Rhoades, Harmony; Goldbach, Jeremy T
Abstract : Introduction: Sexual minority adolescents (SMA) report higher rates of anxiety, self-harm, depression and suicide than heterosexual peers. These disparities appear to persist into adulthood and may worsen for certain subgroups, yet the mechanisms that drive these concerns remain poorly understood. Minority stress theory, the predominant model for understanding these disparities, posits that poorer outcomes are due to the stress of living in a violently homophobic and discriminatory culture. Although numerous studies report associations between minority stress and behavioural health in adolescence, no study has comprehensively examined how minority stress may change throughout the course of adolescence, nor how stress trajectories may predict health outcomes during this critical developmental period. Methods and analysis: Between 15 May 2018 and 1 April 2019, we recruited a US national sample of diverse SMA (n=2558) age 14–17 through social media and respondent-driven sampling strategies. A subset of participants (n=1076) enrolled in the longitudinal component and will be followed each 6 months until 1 July 2022. Primary outcomes include symptoms of depression, anxiety and post-traumatic stress disorder; suicidality and self-harm and substance use. The key predictor is minority stress, operationalised as the Sexual Minority Adolescent Stress Inventory. We will use parallel cohort-sequential latent growth curve models to test study hypotheses within a developmental framework. Ethics and dissemination: All participants provided assent to participate, and longitudinal participants provided informed consent at the first follow-up survey after reaching age 18. All study procedures were reviewed and approved by the University of Southern California Social–Behavioral Institutional Review Board, including a waiver of parental permission given the potential for harm due to unintentional 'outing' to a parent during the consent process. The final anonymous data set will be available on request, and research findings will be disseminated through academic channels and products tailored for the lay community.